2017
DOI: 10.1111/cdev.12828
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Correlates of Gender Role Orientations in African‐American Youth

Abstract: This study charted the development of gendered personality qualities, activity interests, and attitudes across adolescence (approximately ages 9-18) among 319 African-American youth from 166 families. The relations between daily time spent with father, mother, and male and female peers-the gendered contexts of youth's daily activities-and (changes in) these gender role orientations were also assessed. Boys and girls differed in their gender role orientations in stereotypical ways: interest in masculine and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Shortly thereafter, children often show preferences for toys and clothing stereotypically associated with their genders (Campbell et al, 2000; Davis & Hines, 2020; Halim et al, 2014; Jadva et al, 2010; Serbin et al, 2001) and prefer same-gender peers (Martin et al, 2011; McHale et al, 2004). Children’s preference for gender stereotypical objects, activities, and same-gender peers are generally observed throughout childhood and adolescence, though the degree to which they show these preferences varies across developmental stages (Kanka et al, 2019; Skinner & McHale, 2018; for a review see Halim et al, 2011). While most youth show these patterns, there is variation, wherein some youth show strongly gendered identity and preferences, others show weaker identity and preferences, and still others come to identify and/or have preferences more often associated with another gender (Golombok & Rust, 1993; Golombok et al, 2012; Gülgöz et al, 2019; Martin & Ruble, 2010).…”
Section: Stability Of Gender Concepts In Middle Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly thereafter, children often show preferences for toys and clothing stereotypically associated with their genders (Campbell et al, 2000; Davis & Hines, 2020; Halim et al, 2014; Jadva et al, 2010; Serbin et al, 2001) and prefer same-gender peers (Martin et al, 2011; McHale et al, 2004). Children’s preference for gender stereotypical objects, activities, and same-gender peers are generally observed throughout childhood and adolescence, though the degree to which they show these preferences varies across developmental stages (Kanka et al, 2019; Skinner & McHale, 2018; for a review see Halim et al, 2011). While most youth show these patterns, there is variation, wherein some youth show strongly gendered identity and preferences, others show weaker identity and preferences, and still others come to identify and/or have preferences more often associated with another gender (Golombok & Rust, 1993; Golombok et al, 2012; Gülgöz et al, 2019; Martin & Ruble, 2010).…”
Section: Stability Of Gender Concepts In Middle Childhoodmentioning
confidence: 99%
“…We tested for differences between groups and examined whether boys and girls differ in their gender development over time. Because research has suggested that the strength of gender-typed preferences might vary over time (Skinner & McHale, 2018), we also explored whether the length of time between the assessments affected the stability of gender preferences.…”
Section: The Present Researchmentioning
confidence: 99%
“…In addition to parents' gender, associations between marriage and parent-child relationships may also differ for sons and daughters. Adolescent girls may be more attuned to family experiences and thus more likely to be affected by interparental dynamics given that, on average, they are higher in relationally oriented, expressive traits compared to boys (Skinner & McHale, 2018). Scholars also have highlighted the vulnerability of boys in the face of marital hostility (Cox et al, 2001); however, given that they may be more likely to intervene in the face of parental conflict (Sturge-Apple et al, 2004).…”
Section: Moderators Of Linkages Between Marital and Parent-child Rela...mentioning
confidence: 99%
“…Boys, in contrast, reported more sibling positivity on occasions when parents reported more conflict than usual. These results suggest that sisters may be more vulnerable to marital disharmony than brothers, possibly reflecting that girls tend to be higher in expressive qualities than boys (Skinner & McHale, 2018) and so particularly sensitive to parents' marital issues. In contrast, boys may have compensated for parents' marital disharmony by turning to their siblings for support.…”
Section: Discussionmentioning
confidence: 94%
“…First, sisters report closer sibling relationships than brothers, on average (Kim et al, 2006; Whiteman et al, 2015). Further, Black girls, similar to girls of other racial/ethnic groups, tend to exhibit more relationally oriented, expressive traits compared with boys, and these traits that may make them particularly sensitive to their parents' marital experiences (Skinner & McHale, 2018).…”
Section: The Roles Of Parent and Youth Gender In Marital–sibling Rela...mentioning
confidence: 99%